Dimensi Gaya Hidup dan Motivasi Simbolik dalam Pemilihan Desain Helm - Samsul Arifin; Achmad Ali Yafi K (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This literature study examines the relationship between lifestyle dimensions, purchase motivation, and helmet design as a medium for consumer self-expression. As a product with dual functions, helmets are required to meet safety standards while simultaneously serving as a vehicle for communicating personal and social identity. The analysis is built upon a synthesis of concepts from consumer behavior theory, lifestyle studies, and product design literature. The findings reveal that lifestyle values are internalized into design preferences through mechanisms of identification with reference groups and social learning within communities. Visual elements such as shape, color, graphics, material, and brand function as a symbolic vocabulary that consumers use to construct and project their identity. Purchase motivation is driven by symbolic needs for social recognition, group affiliation, self-differentiation, and emotional satisfaction, which often override functional considerations in the final decision-making process. A successful helmet design is one that resonates with the consumer's self-narrative, transforming a mandatory safety device into a meaningful personal statement. This study contributes a conceptual framework for understanding symbolic consumption in the context of protective gear and offers theoretical foundations for future empirical research on consumer behavior and product design.